Flocculation of oil-in-water emulsions stabilised by milk protein ingredients under gastric conditions: Impact on in vitro intestinal lipid digestion. (March 2019) - Wang, Xin; Lin, Quanquan; Ye, Aiqian; Han, Jianzhong; Singh, Harjinder
Abstract: The effect of the gastric behaviour of protein-stabilised oil-in-water emulsions on intestinal lipid digestion was investigated using an in vitro dynamic gastric digestion model ‒ the human gastric simulator (HGS) and an intestinal model. Emulsions were prepared using milk protein concentrate (MPC), calcium-depleted MPC or sodium caseinate. In the MPC-stabilised emulsion, flocculation, induced by the milk-clotting enzyme pepsin, occurred after 10 min of digestion (at pH > 6) in the HGS. Closely knitted flocs of large size, which remained in the HGS throughout the gastric digestion, were formed. However, in emulsions stabilised by calcium-depleted MPC or sodium caseinate, flocculation occurred after approximately 40 min of digestion because of the low pH (∼pH 5); the flocs were relatively small and disintegrated after further digestion. The particle sizes of the gastric digesta mixtures obtained at each digestion time were in the order: MPC emulsion > calcium-depleted MPC emulsion > sodium caseinate emulsion. In contrast, the oil contents of the mixtures were in the order: MPC emulsion < calcium-depleted MPC emulsion < sodium caseinate emulsion, suggesting that the MPC emulsion had a slower release of oil droplets into the intestine than the calcium-depleted MPC and sodium caseinate emulsions. In the intestinal phase, the extent of lipid digestion followed the order: MPC emulsion < calcium-depleted MPC emulsion ≤ sodium caseinate emulsion. The results suggested that the structures and the size of the flocs induced by interactions between milk proteins and pepsin or acid during the gastric digestion of emulsions influence intestinal lipid digestion. Graphical abstract: Image 1 Highlights: Emulsions were digested in an in vitro dynamic gastric model (HGS) and an intestinal model. MPC emulsions flocculated with large flocs induced by pepsin at pH > 6. Calcium-depleted MPC or caseinate emulsions flocculated with small flocs at low pH. The distinct gastric behaviours of these emulsions affect the lipolysis in the intestine.